Decomposing the Gender Wealth Gap in Ecuador. (August 2017) - Anglade, Boaz; Useche, Pilar; Deere, Carmen Diana
Highlights: The gender wealth gap for Ecuador varies across the wealth distribution. Our results contrast with those for developed countries. The gap favoring men is larger among sole heads than partnered heads of household. Among both samples, at the lower tail, the gap is mostly due to returns to covariates. At the median and upper quantiles, differences in endowments drive the gap. Abstract: Unlike the gender earnings gap that has been amply studied, the gender wealth gap has only recently begun to receive attention. Studies of the gender wealth gap have been concentrated on developed countries and have been limited by the use of household-level data. Using individual-level and sex-disaggregated wealth data for Ecuador, this paper examines the pattern of wealth inequality across genders, at different points of the wealth distribution, for sole and then partnered household heads. We use a new Oaxaca-Blinder-type decomposition method based on unconditional quantile regression to investigate the sources of the gap at different quantiles. Our results show that among sole heads the gap favors men across the distribution and is largest at the lower tail. Among partnered heads, the gap is much less pronounced throughout the distribution, actually reverting at the lower tail. For both sole and partnered heads, at the lower tail of the distribution, the gender gap is primarily associated with differing returns to covariates. At the median and upper quantiles, gender differences in endowments (ownership of savings accounts, education, and age) drive the gap. Gender bias in inheritance plays a significant role only at lower and median wealth levels. Overall, our results show stark contrasts with results for developed countries and important differences between sole versus partnered heads. Our study also adds evidence to the long-standing debate over whether female household heads are poorer than male heads and calls for the pursuit of wealth-differentiated policies and social programs to increase women's participation in the formal economy, as well as the returns to their participation.